MEMES RELATED TO COVID-19 ON SOCIAL MEDIA: A STUDY - Mandeep Choursia, Dr. Chanchal Sachdeva Suri (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
COVID-19 is the talk of the town presently in the whole world and the world is busy to deal with it so they can break the chain of spreading this disease amongst its citizens. For the safety of the people, most of the countries of the globe declared this as the state of emergency and announced the complete lockdown. Now, most of the population of the world is in quarantine and the best option available for them is the internet on which they could spend time interacting with people or surf it for gathering information on current affairs. Many memes are being made on COVID-19 and spread on various sites like Facebook, Instagram, Youtube etc. People are coming across the content made upon the present situation. Now the question arises, how many people actually like and share these memes further? This study is based on the aspect which focuses on social platform(s) most popular for memes at present. Also the researcher will study, how many users like and share these memes. The methodology used for the present study will be google survey as no other methodology is possible to adopt. The sample selected for the study will be the population of Tricity i.e Chandigarh, Mohali and Panchkula.